Tree species-specific strategies of soil aggregation driven by SOC–GRSP coupling under nitrogen addition and precipitation reduction - Mingxin Zhou; Yibo Li; Wei Liu; Chao Jia; Jiantao Hao (PLoS ONE, 2026)
Soil structural stability underpins ecosystem function, yet how nitrogen (N) enrichment and precipitation reduction jointly regulate glomalin-related soil proteins (GRSP) and aggregate formation in temperate forests remains poorly understood. This knowledge gap limits predictions of soil carbon persistence under global change. A factorial field experiment was conducted in an old-growth temperate forest with four treatments (CK, + N, –P, + N–P) across three dominant tree species. Rhizosphere soils were analyzed for total and easily extractable GRSP (T-GRSP, EE-GRSP), aggregate-size distribution, and physicochemical properties. Random forest modeling and structural equation modeling (SEM) were used to identify key regulatory pathways. N addition significantly increased EE-GRSP (3.92–5.74 mg g ⁻ ¹) and macroaggregates (4–8 mm: 21.6%–34.8%), while precipitation reduction reduced EE-GRSP (by 36.5%) and increased microaggregates (0.053–0.25 mm: + 29.3%). soil organic carbon (SOC) was strongly and positively correlated with EE-GRSP (R² = 0.69–0.63), T-GRSP (R² = 0.82–0.77), MWD (R² = 0.85–0.67), and GMD (R² = 0.84–0.72). Random forest identified EE-GRSP and SOC as dominant predictors of aggregate stability. SEM revealed that SOC regulated GRSP and MWD through NH₄ ⁺ –N and SWC (Fig. 2–5). Our findings highlight a coupled “carbon–protein–structure” pathway in regulating soil aggregation. The regulatory effects of N and water are both species-specific and pathway-integrated, emphasizing the role of SOC-mediated GRSP dynamics in sustaining soil physical integrity under climate perturbations.